Diagnosis and treatment of small bowel cancer - B. M. Rakhimov; E. P. Krivoshchekov; A. N. Kirsanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Background. Tumors of the small intestine are difficult to diagnose. Their preoperative detection is an exception rather than the rule.Materials and methods. We examined 15 patients preoperatively diagnosed with small bowel tumors. Patients were selected for two-stage enterography according to special criteria. Before examination, patients received prokinetic agents to enhance gastrointestinal motility. After placing the probe in the initial segment of the small intestine, we connected a special device for remote mechanical administration of contrast agent (0.1 kg/cm2, which is equal to 100 mL/min). To prevent overextension of the intestine, we administered contrast by portions. After reaching the middle part of the ileum, we introduced a portion of air. Monitoring of the diagnostic process was performed by short-term radiographic inspection and imaging.Results and discussion. Multislice computed tomography enterography is currently considered as one of the most informative methods. It is a highly sensitive method for the diagnosis of small bowel tumors. However, a tailored approach should be used during examination with the consideration of gastrointestinal motility.Conclusion. Multislice computed tomography enterography has a number of advantages over conventional enterography.Small bowel tumors that are not associated with clinical signs of acute intestinal obstruction may remain undiagnosed for a long time and treated as any other gastrointestinal diseases.Surgical treatment of small bowel tumors remains the main therapeutic measure for patients.